PEMBUATAN PROTOTIPE APLIKASI PEMILIHAN MATAKULIAH TERBAIK UNTUK DIAMPUH MAHASISWA DALAM PROSES PENGISIAN KARTU RENCANA STUDI: DEVELOPMENT OF THE BEST COURSE SELECTION APPLICATION PROTOTYPE FOR STUDENTS TO BE EMPLOYED IN THE STUDY PLAN CARD FILLING PROCESS - Julius Panda Putra Naibaho (Universitas Papua, 2014)
When the KRS time, student choose subject for their study in one semester. Sometimes student do not know best subject for their KRS because they forget about their academy result. This condotion is not good for KRS process. My reseach is try to handle this problem. My application is present the best subject for student in their KRS. student choose subject for their KRS from first semester to the last semester and student have to repeat (take again) if student do not pass the subject in last semester. this pattern is the key to make an application to present the best subject for their KRS.